Optimizing chromosome dispersion quality: the key role of cell density - Chao-Xian Gao; Li-Mei Li; Yu-Ting Chen; Ying-Yan Guo; Bo-Xin Li; Xue-Qin Yang; Chang-Ye Hui (Frontiers in Cell and Developmental Biology)
ObjectiveThis study aims to optimize metaphase dispersion in automated detection by quantitatively determining the optimal cell suspension density to enhance the accuracy and efficiency of chromosomal aberrations analysis.MethodsLymphocyte metaphase suspensions were prepared using an automated harvesting system and subjected to a concentration gradient of 104–107 cells/mL. Metaphase images were captured using an automated chromosome scanning and analysis system, and cell density, suspension turbidity, metaphase counts, and dispersion area were measured to quantitatively assess the impact of cell density on metaphase dispersion quality. The practical application of turbidity-based density adjustment was further validated.ResultsThe study found that a cell density of 1.04 × 106 cells/mL and suspension turbidity of 0.21 McFarland (McF) yielded the preferred metaphase dispersion, sufficient metaphase counts, and maximum dispersion area, significantly reducing chromosome crossover and overlap. Turbidity adjustment enabled consistent dispersion effects across different initial densities, markedly improving the uniformity of metaphase dispersion.ConclusionThis study innovatively established a turbidity-based cell density adjustment method, clarifying the impact of cell density on metaphase dispersion through quantitative means and providing standardized technical support for automated detection. This method effectively addresses the inconsistency in metaphase dispersion due to varying cell densities in automated detection, offering a significant basis for homogenizing detection results across laboratories and advancing the standardization and homogenization of chromosomal aberrations analysis techniques.